Uniconazole Augments Abscisic Acid in Promoting Somatic Embryogenesis in Cotton (Gossypium hirsutum L.) - Chen, Yanli; Yu, Hongxia; Wang, Ye; Li, Fuguang; Xing, Yadi; Ge, Xiaoyang (Frontiers in Plant Science, 2022)
During somatic embryogenesis (SE), somatic cells initiate embryogenic development under appropriate conditions. Uniconazole, a plant growth-regulator, was found to inhibit the proliferation of callus but promoted the conversion of callus into embryogenic callus (EC) in cotton. The supplementation of uniconazole in the culture medium significantly suppressed endogenous auxin (IAA) level in callus tissues in both the callus initiation and proliferation stage, but enhanced ABA level only in the callus proliferation stage. Exogenous ABA and uniconazole showed cooperative effects on promoting the differentiation rate of callus into EC. These findings were verified by RNA-seq analysis, which elucidated that the genes involved in the IAA biosynthesis, metabolism and signaling, and ABA metabolism pathways were regulated by uniconazole during the callus development and somatic embryogenesis. Overall, the results suggest that uniconazole could modulate callus proliferation and callus differentiation rate by regulating the endogenous levels of IAA and ABA.